Isolation of genomic clones of UDP-N-acetylglucosamine pyrophosphorylase (AGX) from kelampayan (neolamarckia cadamba) - Tiong, Yong Wei (Universiti Malaysia Sarawak (UNIMAS), 2013)
Neolamarckia cadamba or locally known as Kelampayan is an evergreen and tropical tree native to South Asia. Kelampayan possesses great economic and' commercial value as its timber is the best raw materials for plywood industry. UDP-N-acetylglucosamine pyrophosphoryJase (AGX) gene is a key enzyme used for the cell wall formation in chitin synthesis pathway. The presence of chitin helps in providing tensile strength of the cell wall that is required to maintain turgor and compensation mechanism activated by cell wall damage. In this study, the isolation of genomic clones of AGX gene from N. cadamba was studied. The main objective was to isolate the genomic clones of AGX gene from N cadamba. The targeted DNA sequence of AGX gene was amplified with the designed primer pair based on EST sequence which was obtained from EST of Neolamarckia cadamba (NcdbEST) by using Polymerase Chain Reaction (PCR) technique. The genomic sequences of AGX gene were subjected to nucleotide BLAST (BLASTn) analysis to search for homology sequence and validate the identity of the obtained sequences through NCB I. Unfortunately, the AGX genomic sequences did not show similarity to AGX gene but having similarity towards Aquaporin gene. Therefore, the desired primers obtained from NcdbEST need to be redesigned for other researches that involved in using AGX gene in future.